Comparative Analysis of ORM Systems for the .NET Platform - Tomasz Wiatrowski (Journal of Computer Sciences Institute)
This article presents a comparative study of three popular ORM (Object-Relational Mapping) systems used in the .NET technology: Entity Framework Core, Dapper, and LINQ to DB. The analysis is divided into two main parts: theoretical, focusing on research found in literature, and practical, where an application was implemented to assess the performance of each system and their memory consumption. The results obtained were presented in the form of graphs. Dapper emerged as the most efficient system and consumed the least memory in the majority of test cases.